Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Microbial markers of resilience and its correlation with reproductive performance in lactating sows under heat stress condition - Abdolreza Hosseindoust; Jun Young Mun; Sang Hun Ha; Habeeb Tajudeen; Priscilla Neves Silvestre; Jae Cheol Jang; Jin Soo Kim (Tropical Animal Health and Production, 2026)

Environmental factors on microalgal resuspension and dynamics in tidal flats on the west coast of Korea - Hosang Kim; Junghyun Lee; Hun Jun Ha; Sun Min Choi; Yangrae Rho; Jinsoon Park; Ho Kyung Ha; Bong-Oh Kwon; Jong Seong Khim (Marine Pollution Bulletin, 2026)

Single-tube total analysis system for ratiometric detection of exosomal miRNAs in breast cancer diagnosis - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Ha Rim Ahn; Young Jo Kim; Jeong-Woo Choi; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2026)

Enhanced settling velocity and floc formation in response to dredging-induced plumes: In-situ observations from a coastal sand mining site - Seong Woon Jeong; Hun Jun Ha; Ho Kyung Ha (Regional Studies in Marine Science, 2025)

Identification of candidate genes associated with resistance to Heterodera sojae in soybean - Heonil Kang; Jiyong Song; Hyoung-Rai Ko; Jae Eun Jo; Ji-Hun Hwang; Yeon-Ki Kim; Soo-Kwon Park; Gyu Tae Park; Tae-Hwan Jun; Bo-Keun Ha; Zenglu Li; Kyung Do Kim (Theoretical and Applied Genetics, 2025)

Impacts of consecutive typhoons (Maysak and Haishen in 2020) on the benthic processes of a mega-tidal flat in highly developed area - Seong Woon Jeong; Hun Jun Ha; Hosang Kim; Beomgi Kim; Jong Seong Khim; Ho Kyung Ha (Marine Pollution Bulletin, 2025)

Prevalence and virulence profiles of ESBL-producing Escherichia coli in urinary and blood infections in South Korea - Jong-Hun Ha; Jeong-Ih Shin; Kyu-Min Kim; Jeong-Gyu Choi; Minh Phuong Trinh; Won Jun Anh; Kyung-Min Kang; Hyung-Lyun Kang; Jung-Hyun Byun; Wongwarut Boonyanugomol; Kee Woong Kwon; Myung Hwan Jung; et al. (Folia Microbiologica, 2025)

Hourglass-inspired total analysis system for the sensitive colorimetric detection of exosomal miRNA using the CRISPR-Cas12a system with isothermal amplification - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Jeong-Woo Choi; Ha Rim Ahn; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2025)

Effects of dietary mineral level and creep feed provision on lactating sows during heat stress - Sang Hun Ha; Min Ju Kim; Jun Young Mun; Abdolreza Hosseindoust; Tajudeen Habeeb Temitope; So Dam Choi; Seon Ah Park; Priscilla Neves Silvestre; Sang Sik Lee; Jin Soo Kim (Tropical Animal Health and Production, 2025)

Dynamic behaviors of suspended sediment and chlorophyll-a in intertidal flats under episodic meteorological events - Hun Jun Ha; Jong Seong Khim; Ho Kyung Ha (Marine Geology, 2024)

Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Su In Kim; Jun Young Seo; Jae-Hun Park; Pyeong Joong Kim; In Gwon Kim; Kyung Man Kim; Ho Kyung Ha (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominantly seaward due to tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry between flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.

Benthic sediment disturbances by episodic human-controlled discharge in an altered estuary - Seong Woon Jeong; Hun Jun Ha; Kyung Man Kim; Ho Kyung Ha (Marine Geology, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Comparison of Methods for Determining Erosion Threshold of Cohesive Sediments Using a Microcosm System - Hun Jun Ha; Ho Kyung Ha (Frontiers in Marine Science, 2021)
Erosion of cohesive sediments is a ubiquitous phenomenon in estuarine and intertidal environments. Several methods have been proposed to determine the surface erosion threshold (τ c0 ), which are still debatable because of the numerous and uncertain definitions. Based on erosion microcosm experiments, we have compared three different methods using (1) eroded mass (EM), (2) erosion rate (ER), and (3) suspended sediment concentration (SSC), and suggested a suitable method for revealing the variation of erodibility in intertidal sediments. Erosion experiments using a microcosm system were carried out in the Muuido tidal flat, west coast of South Korea. The mean values of τ c0 for three methods were: 0.20 ± 0.08 Pa (EM); 0.18 ± 0.07 Pa (ER); and (3) 0.17 ± 0.09 Pa (SSC). The SSC method yielded the lowest τ c0 , due to the outflow of suspended sediment from the erosion chamber of the microcosm. This was because SSC gradually decreased with time after depleting the erodible sediment at a given bed shear stress (τ b ). Therefore, the regression between SSC and applied τ b might skew an x -intercept, resulting in the underestimation (or “not-determined”) of τ c0 . The EM method yielded robust and accurate (within the range of τ b step at which erosion begins) results. The EM method represents how the erodible depth thickens as τ b increases and therefore seems better suited than the SSC and ER methods for representing depth-limited erosion of cohesive sediments. Furthermore, this study identified the spatiotemporal variations of τ c0 by EM method in an intertidal flat. The τ c0 in mud flat was about two times higher than that in mixed flat. Compared to the end of tidal emersion, the sediment was 10–40% more erodible at the beginning stage.

Using end-member analysis to determine sediment dispersal and depositional processes on the Heuksan mud belt, southwest Korean shelf - Hun Jun Ha; Tae Soo Chang; Ho Kyung Ha (Geo-Marine Letters, 2021)

Anti-inflammatory activity of the extracts from Rodgersia podophylla leaves through activation of Nrf2/HO-1 pathway, and inhibition of NF-κB and MAPKs pathway in mouse macrophage cells - Ha Na Kim; Jeong Dong Kim; Su Bin Park; Ho-Jun Son; Gwang Hun Park; Hyun Ji Eo; Hyun-Seok Kim; Jin Boo Jeong (Inflammation Research, 2020)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Behavior, PET and histology in novel regimen of MPTP marmoset model of Parkinson’s disease for long-term stem cell therapy - Jun-Won Yun; Jae-Bum Ahn; Euna Kwon; Jae Hun Ahn; Hyung Woo Park; Hwon Heo; Jin-Sung Park; Hyeonjin Kim; Sun Ha Paek; Byeong-Cheol Kang (Tissue Engineering and Regenerative Medicine, 2016)

Factors controlling mud accumulation in the Heuksan mud belt off southwestern Korea - Tae Soo Chang; Hun Jun Ha; Seung Soo Chun (Geo-Marine Letters, 2015)

The Heuksan mud belt on the tide-dominated shelf of Korea: a supply-driven depositional system? - Tae Soo Chang; Hun Jun Ha (Geo-Marine Letters, 2015)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

Cerebellar Atrophy in Patients with Subcortical-Type Vascular Cognitive Impairment - Cindy W. Yoon; Sang Won Seo; Jun-Sung Park; Ki-Chang Kwak; Uicheul Yoon; Mee Kyung Suh; Geon Ha Kim; Ji Soo Shin; Chi Hun Kim; Young Noh; Hanna Cho; Min-Jeong Kim; et al. (The Cerebellum, 2013)